The Impact of Transfer from Hemodialysis on Peritoneal Dialysis Technique Survival. Issue 3 (May 2015) - Nessim, Sharon J.; Bargman, Joanne M.; Jassal, S. Vanita; Oliver, Matthew J.; Na, Yingbo; Perl, Jeffrey
Background: A significant proportion of peritoneal dialysis (PD) patients receive an initial period of hemodialysis (HD) before transitioning to PD ("PD-switch"). We sought to better understand the risks of PD technique failure (TF) and mortality for those patients compared with patients starting with PD as their first dialysis modality ("PD-first"). Methods: Using Canadian Organ Replacement Register data, we compared the risk of PD TF between PD-first and PD-switch patients within the first year after HD initiation. In a secondary analysis, the PD-switch patients were stratified into three groups based on timing of the switch from initial HD to PD as follows: 0 – 90 days, 91 – 180 days, and 181 – 365 days. Each group was compared with PD-first patients for risk of PD TF and death. Results: Between 2001 and 2010, 9404 patients initiated PD as their first renal replacement therapy, and 3757 switched from HD to PD. After multivariable adjustment, the risk of PD TF was higher among PD-switch patients than among PD-first patients [adjusted hazard ratio (AHR): 1.37; 95% confidence interval (CI): 1.26 to 1.49], particularly within the first year after the switch from HD to PD (AHR: 1.51; 95% CI: 1.36 to 1.68). There was no association between time on HD within the first year and subsequent risk of PD TF. For all the stratified PD-switch groups, death rates were higher than those for PD-first patients. Conclusions: Compared with patients who start renal replacement therapy with PD, those who transfer from HD to PD within the first year on dialysis experience higher rates of PD TF and death, with the highest risk being observed in the initial year after the switch to PD.